2016
DOI: 10.1177/1352458516663033
|View full text |Cite
|
Sign up to set email alerts
|

Does robot-assisted gait training improve ambulation in highly disabled multiple sclerosis people? A pilot randomized control trial

Abstract: RAGT improved the walking competencies in non-autonomous ambulant patients with MS, with benefits in terms of perceived fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 36 publications
1
61
1
Order By: Relevance
“…Overall, the authors found that robot-assisted gait training might be beneficial to people with progressive MS. However, none of the treatment methodologies had a significant effect on perceived fatigue, which differs from other studies [83,108]. One explanation advanced by the authors is that the FSS might not be reliable while measuring high levels of fatigue.…”
Section: Measuring and Analyzing Fatigue In Rehabilitationcontrasting
confidence: 72%
See 3 more Smart Citations
“…Overall, the authors found that robot-assisted gait training might be beneficial to people with progressive MS. However, none of the treatment methodologies had a significant effect on perceived fatigue, which differs from other studies [83,108]. One explanation advanced by the authors is that the FSS might not be reliable while measuring high levels of fatigue.…”
Section: Measuring and Analyzing Fatigue In Rehabilitationcontrasting
confidence: 72%
“…A study conducted by Pompa et al found similar result with robot assisted gait training. Although, people who underwent conventional walking training did not show an improvement in subjective fatigue [83]. Straudi et al on the other hand did not find significant improvement in the perceived fatigue during robot assisted gait training [109].…”
Section: Measuring and Analyzing Fatigue In Rehabilitationmentioning
confidence: 92%
See 2 more Smart Citations
“…We showed that patients with high levels of disability were able to complete GXT in 10 out of 25 occasions (40% success rate) and 50% of our participants achieved 90% of their age-predicted maximal heart rates during GXT, potentially important information needed for planning of future studies among patients with high levels of MS-related disability [26,78,82,84,85,[87][88][89][90][91][92]. We found that our participants with high disability achieved 12.2% greater maximal workload during GXT as a result of training, despite small increases in maximal heart rate (1.8%), maximal respiratory exchange ratio (2.2%), and maximal V O 2 (6.6%).…”
Section: Ability To Perform Gxt and Improvements In Cardiorespiratorymentioning
confidence: 70%